PEMBENTUKAN BADAN USAHA MILIK DESA DI KECAMATAN RENGAT BARAT KABUPATEN INDRAGIRI HULU BERDASARKAN PERATURAN DAERAH KABUPATEN INDRAGIRI HULU NOMOR 5 TAHUN 2011 TENTANG BADAN USAHA MILIK DESA - Harun Al Rasyid; Mexsasai Indra; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The Village, has several community institutions, one of them is theVillage-Owned Enterprise (VOE). Based on Article 3 of the Regional Regulationof Indragiri Hulu Regency Number 5 of 2011 concerning Village-OwnedEnterprises, VOE is formed with the aim of gaining profit to strengthen theOriginal Village Revenue; Advancing village economy; Increase the villagecommunity welfare; and improve the management of existing village assets, suchas village treasury land management. From this objective, it can be seen thatVOE functions as an engine of the village economy and the welfare of the villagecommunity.This type of research is empirical juridical research or sociological legalresearch which is a research approach that emphasizes legal aspects related tothe subject matter to be discussed, associated with reality on the ground. Theresearch was conducted in VOE in the West Rengat sub district of Indragiri HuluRegency, while the sample population is all parties related to the problem understudy. The data sources used are primary data and secondary data, the datacollection techniques in this research are by observation, questionnaire,interview, and literature review.From the results of this research, there are three main things that can beconcluded: First, the implementation of the establishment of village-ownedbusiness entities in 6 (six) villages in the western Rengat sub-district of IndragiriHulu Regency has been carried out which have been poured into VillageRegulations but are problematic in the process of formation. Second, theobstacles in establishing a village-owned business entity include the low quality ofhuman resources (HR), which results in the inoperability of the basic duties andfunctions of the village head, the village apparatus not being empowered, lack ofcoordination with related parties and village deliberation, lack of publication ofVillage Regulations on VOE, and the absence of Village Regulations on thecapital participation of VOE. Third, the efforts going forward carried out by thevillage government related to the legality of VOE are to allocate a budget forhuman resource quality improvement programs, revise the Village Regulationsabout the establishment of VOE, conduct village deliberations, coordinate withrelated parties, and empower the potential of the village.Keywords: Establishment – Village – Owned Enterprises – West Rengat